2016
DOI: 10.18632/oncotarget.13156
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in nuclear prelamin a recognition factor-like causes diffuse pulmonary arteriovenous malformations

Abstract: Two daughters in a Chinese consanguineous family were diagnosed as diffuse pulmonary arteriovenous malformations (PAVMs) and screened using whole exome sequencing (WES) and copy number variations (CNVs) chips. Though no mutation was found in the established causative genes of capillary malformation-AVMs (CM-AVMs) or PAVMs, Ser161Ile (hg19 NM_022493 c.482G>T) mutation in nuclear prelamin A recognition factor-like (NARFL) was identified. Ser161Ile mutation in NARFL conservation region was predicted to be deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…IHC was performed as previously described [37]. Staining intensity and proportion were viewed and expression scores were calculated [38].…”
Section: Methodsmentioning
confidence: 99%
“…IHC was performed as previously described [37]. Staining intensity and proportion were viewed and expression scores were calculated [38].…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR/Cas9-mediated narfl knockout was described in our previous work [9]. Two independent mutant lines, respectively containing 4 bp insertion and 5 bp deletion plus 4 bp insertion in the target region, were obtained and confirmed by sequencing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that NARFL knockdown in mammalian cells causes increased levels of hypoxia-inducible factor-1α (HIF-1α) protein under normoxic and hypoxic conditions [7], and recent study has shown that NARFL is a key element in cellular defense against oxidative stress [8]. In our previous work, NARFL (Ser161Ile) was identified as a causative gene in a family with diffuse pulmonary arteriovenous malformations (dPAVMs), in which the proband died of pulmonary hypertension at a young age, and we observed abnormal development of the subintestinal vessels using a narfl -knockout zebrafish model [9]. Previous studies provide insights regarding the interaction between oxidative stress, angiogenesis and vascular diseases, indicating that oxidative stress plays a positive role during angiogenesis [[10], [11], [12], [13]].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, our understanding of lung cancer is very limited, which has resulted in poor patient outcomes. Discovery of new targeted biomarkers for prognosis is important in cancer research (4)(5)(6). Recently, accumulating studies have revealed that angiogenesis-related genes, including DLL4 are dysregulated in lung cancer and they act as oncogenes or tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%